French adaptation and validation of the Sino‐Nasal Outcome Test‐22: a prospective cohort study on quality of life among 422 subjects. (February 2015) - de Dorlodot, C.; Horoi, M.; Lefebvre, P.; Collet, S.; Bertrand, B.; Eloy, P.; Poirrier, A.‐L.
<x xml:space="preserve">Abstract</x> Objectives ENT surgeons are facing an ever‐increasing demand to demonstrate their efficacy. The 22‐item Sino‐Nasal Outcome Test (SNOT‐22) is a fully validated and easy‐to‐use outcome measure in rhinology. Our goal was to translate and validate the SNOT‐22 in a cohort of 422 French‐speaking subjects. Design, Setting and Participants The French version of the SNOT‐22 was obtained by forward and backward translations by six independent interpreters. Five experienced rhinologists compared the translations to each other, and a group of 12 naive patients selected the most appropriate translation of each item. To evaluate this questionnaire, we conducted a prospective cohort study on 376 rhinological patients and 46 healthy volunteers in three University‐affiliated teaching Hospitals. Main outcome measures Reproducibility (test–retest reliability), internal consistency, known‐group differences, responsiveness to treatment, validity and correlation to other clinical instruments (visual analogue scale, Nasal Obstruction Symptoms Evaluation score and Lund–Mackay score). Results The test–retest reliability coefficient was 0.78, indicating a good reliability when administering the instrument on two different occasions. The internal consistency was high with a Cronbach's α value of 0.93. Our questionnaire was able to detect differences between rhinological patients and control subjects (P < 0.0001) and improved significantly after nose and sinus surgery (P < 0.0001), indicating a good responsiveness. There was a relative correlation with visual analogue scale and Nasal Obstruction Symptoms Evaluation (NOSE) score, but no correlation with Lund–Mackay score. Conclusion The SNOT‐22 is a reliable and valid tool to assess quality of life in French‐speaking patients and correlates well with known indices of disease severity.